Emergence of Toxin A-Negative, Toxin B-Positive Clostridium Difficile Strains: Epidemiological and Clinical Considerations - King, Amy M; Mackin, Kate E; Lyras, Dena (Future microbiology, 2015)
[...]there has been a decrease in the prevalence of C. difficile disease, and specifically 027 strains, in North America and Europe [8], although other strain types, such as toxinotype V/ribotype 078, are now becoming more prevalent and more common in community-acquired infections [8,9]. Financial & competing interests disclosure The authors have no relevant affiliations or financial involvement with any organization or entity with a financial interest in or financial conflict with the subject matter or materials discussed in the manuscript.